The Knowledge, Attitude, and Practice of Nurses in the Implementation of Atraumatic Care in Hospitalized Children in Indonesia - Nisa, Nafisatun (South East Asia Nursing Research, 2024)
Background: Children's main stresses during hospitalization are separation from family, trauma, pain, and the hospital environment itself, which is unfamiliar to them. Atraumatic care is therapeutic care provided through interventions that eliminate or reduce the psychological and physical distress experienced by children and families. The elements impacting nurses' abilities to provide atraumatic care in hospitals are based on person-centered perceptions, knowledge, beliefs, intentions, and attitudes for the outcomes of rational behavior in children with acute illness. Pediatric nurses must provide care on a foundation of atraumatic care.Aim: This study was to explore nurses' knowledge, attitudes, and practices regarding atraumatic care for hospitalized children.Method: The setting of this study is K.R.M.T. Wongsonegoro Regional General Hospital. This study used a cross-sectional and descriptive correlation method, and it observed how nurses implemented atraumatic care. The study sample consisted of 117 nurses, with 70 of them (45 in two pediatric wards and 25 in the PICU) observing their clinical practice. A 25 items Nurses' Practice Scale for Atraumatic Care was used to observe the behaviors of 45 nurses in pediatric wards and 25 nurses in the PICU at work.Results: The post hoc test revealed that nurses in the ER (13.022.71) had significantly greater knowledge in providing atraumatic care. Post hoc comparisons using the Tukey HSD comparison test revealed that nurses in the pediatric ward (99.959.02) had a significantly better attitude toward providing atraumatic care than nurses in the PICU (89.618) and ER (95.948.91). Nurses who were single showed significantly higher attitudes than nurses who were married (z = 1.80, p = 0.04). The Mann-Whitney Test showed that nurses who were working in the pediatric wards (z = -2.80, p = 0.021), female (z = -4.62, p<0.001), and married (z = -2.27, p = 0.02) had significantly practice scores in providing atraumatic care than those who were working in the PICU, male, and single. The Spearman Rank Correlation analysis revealed significant correlations (p-value<0.005) that the more the nurse's knowledge in providing atraumatic care to hospitalized children, the better attitude in providing atraumatic care to hospitalized children, and the more practice in providing atraumatic care.Conclusion: As a result, in order to offer optimal care to hospitalized children, the hospital must provide atraumatic care training for nurses as well as standard operational processes that can assist nurses in implementing atraumatic care and minimizing the impact on hospitalized children.